2009
DOI: 10.1590/s0100-83582009000500010
|View full text |Cite
|
Sign up to set email alerts
|

Planting density of gliricidia when intercropped with corn for weed control

Abstract: Reduced use of herbicides that cause environmental pollution problems is of great interest in modern agriculture. Soil mulching with gliricidia (Gliricidia sepium) branches does not have an allelopathic effect on corn, but decreases weed populations. The objective of this study was to evaluate the effects of gliricidia planting density, when grown as an intercrop, on weed control and corn yield parameters. A randomized block design with split-plots and ten replicates was adopted. Corn cultivars AG 1051 and BM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
2
Order By: Relevance
“…Often, this is not observed. Linhares et al (2009), for example, verified differences between weed control methods on corn yield, but did not see effects of those methods on weed control. Such occasional lack of "parallelism" between the effects on both characteristics (crop yield and weed growth) may be associated with the small sample sizes used in weed growth evaluation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Often, this is not observed. Linhares et al (2009), for example, verified differences between weed control methods on corn yield, but did not see effects of those methods on weed control. Such occasional lack of "parallelism" between the effects on both characteristics (crop yield and weed growth) may be associated with the small sample sizes used in weed growth evaluation.…”
Section: Resultsmentioning
confidence: 98%
“…This implies small experimental precision; consequently, no differences can be detected between weed control methods on growth of those plants. Linhares et al (2009) It can be concluded that "two hoeings [at 20 and 40 days after corn sowing (DACS)] (treatment A)" provided the best baby corn, green corn, and grain yields. The treatment represented by "hoeing at 20 DACS + gliricidia after hoeing (treatment B)" did not differ from treatment A with regard to yield for the three products and was equivalent to the "gliricidia at corn + hoeing at 40 DACS" treatment for green corn yield, but it was superior to it for baby corn weight and grain yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, há indícios de que ocorre o "pegamento" de algumas plantas daninhas após as capinas (Silva et al, 2010a). Resultados semelhantes a esses foram observados por outros autores (Linhares et al, 2009;Silva et al, 2009b), que também estudaram o consórcio milho-gliricídia visando ao controle de plantas daninhas.…”
Section: Resultsunclassified
“…Portanto, das 25 sementes viáveis de gliricí-dia semeadas, apenas 28% deram origem a plantas que sobreviveram até o final do ciclo do milho. Essa redução na população de plantas de gliricídia foi observada por outros autores (Linhares et al, 2009) e pode ser atribuída a vários fatores, incluindo a supressão, em razão da competição interespecífica com o milho e plantas daninhas, além de outros fatores ambientais que usualmente reduzem o estande das culturas (ataque de pragas, profundidade de semeadura inadequada, etc. ).…”
Section: Resultsunclassified